Cochrane Database of Systematic Reviews 2006
DOI: 10.1002/14651858.cd000088.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Family intervention for schizophrenia

Abstract: Background People with schizophrenia from families that express high levels of criticism, hostility, or over involvement, have more frequent relapses than people with similar problems from families that tend to be less expressive of emotions. Forms of psychosocial intervention, designed to reduce these levels of expressed emotions within families, are now widely used. Objectives To estimate the effects of family psychosocial interventions in community settings for people with schizophrenia or schizophrenia-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
307
1
20

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 481 publications
(336 citation statements)
references
References 153 publications
8
307
1
20
Order By: Relevance
“…2 The SEI teams combine assertive community treatment,3 4 psychoeducation,5 and family involvement,6 7 with a low case load of patients for case managers. The early intervention paradigm from which the SEI teams grew is based on the hypothesis of a critical period in the disorder 8…”
Section: Introductionmentioning
confidence: 99%
“…2 The SEI teams combine assertive community treatment,3 4 psychoeducation,5 and family involvement,6 7 with a low case load of patients for case managers. The early intervention paradigm from which the SEI teams grew is based on the hypothesis of a critical period in the disorder 8…”
Section: Introductionmentioning
confidence: 99%
“…Another study, of 19 Italian Mental Health Services (MHS) comparing routine practices and the evidence-based NICE guidelines to promote recovery in schizophrenia (Semisa et al 2008) found that in 60% of MHS no PWS received even three sessions of cognitive therapy per year, while in 40% of MHS less than 10% of PWS received this psychological treatment. As far as family psychoeducation is concerned, the efficacy of this cognitive-behavioral approach -aimed at educating PWS and their relatives about this disorder and improving their communication and problem solving skills -has been demonstrated by more than 50 RCTs and meta-analyses (Pharoah et al 2010). In particular, family psychoeducation has found to have positive impact on the recovery of PWS, with a significant reduction of relapse rates, and improvement in social functioning.…”
Section: Introductionmentioning
confidence: 99%
“…With the current emphasis on community care for mentally ill patients, family intervention, particularly in a group format using a diverse range of modalities, is thought to effectively satisfy the informational needs of families (Cuijpers, 1999) and enhance their coping abilities to care for their relatives with mental illness (Chien and Wong, 2007), thus reducing patient relapses (Pharoah, Mari and Streiner, 2001). Although there have been a few psychological models of commonly used family group interventions, studies seeking to explain which model is most effective have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%